Molecular analysis reveals a new cryptic species in a limpet Lottia kogamogai (Patellogastropoda: Lottiidae) from Japan - Nakayama, Ryo; Sasaki, Takenori; Nakano, Tomoyuki (Zootaxa, 2017)
A group of small lottiid species in Japan, the Lottia kogamogai complex, was phylogenetically analyzed based on the mitochondrial COI gene. As a result, L. kogamogai is subdivided into two geographic clades. Lottia kogamogai s.s. is limited to southern temperate Japan. The northern population formerly considered an intraspecific variation of the species is shown to be a distinct new species, here described as Lottia goshimai n. sp. The new species is distinguishable from L. kogamogai not only genetically, but in radular morphology and shell sculpture.